Linguistic and non-linguistic communication strategies employed by English non-native speaker hosts in talk shows and on-location interviews on SEA Today TV - Izwandi, Alya Afifah; Ira Maisarah; Safnil Arsyad; Alamsyah Harahap (JOALL (Journal of Applied Linguistics and Literature), 2025)
English non-native speaker (NNS) hosts in television broadcasting often face communicative pressures where maintaining fluency, accuracy, and audience engagement is critical. These challenges require the use of compensatory strategies, that is, techniques to overcome gaps in linguistic proficiency and sustain interaction. This study investigates the linguistic and non-linguistic communication strategies employed by NNS hosts on SEA Today TV across two formats: talk shows (TS) and on-location interviews (OL). Using a mixed-methods content analysis, 20 purposively selected broadcast episodes (2021–2025) were examined to represent program variety and host diversity. Data were coded using an adapted version of Farrahi’s (2011) taxonomy, with 20% of the corpus double-coded; inter-rater reliability (Cohen’s κ TS = 1.000; Cohen’s κ OL = 0.875) confirmed coding consistency. The findings identified two main groups of strategies (linguistic and non-linguistic) comprising sixteen subcategories, of which fourteen were observed. Eight strategies, including approximation, elaboration, and body gestures, emerged as a shared “core repertoire.” Contextual contrasts were also evident: talk shows displayed higher reliance on appeal for help and circumlocution due to their collaborative studio setting. At the same time, on-location interviews emphasized elaboration and environmental gestures in response to real-time unpredictability. These results demonstrate that NNS hosts flexibly adapt a stable repertoire of strategies to context-specific demands. Pedagogically, the results suggest that broadcaster training and English as a Lingua Franca (ELF) instruction should explicitly incorporate communication strategy practice. For instance, training modules could simulate on-location unpredictability to help hosts practise elaboration and approximation strategies, while studio-based exercises could focus on appeals for help and interactional alignment with co-hosts and guests. Such targeted activities would strengthen broadcasters’ strategic competence, enabling them to manage linguistic limitations more effectively in diverse communicative settings.